Clonal CTX-M-15-Producing Escherichia coli ST-949 Are Present in German Surface Water - Falgenhauer, Linda; zur Nieden, Anja; Harpel, Susanne; Falgenhauer, Jane; Domann, Eugen (Frontiers in Microbiology, 2021)
Extended-spectrum beta-lactamase (ESBL)-producing bacterial isolates are emerging within the last years. To understand this emergence, a thorough genome-based analysis of ESBL isolates from different sources (One Health approach) is needed. Among these, analysis of surface water is underrepresented. Therefore, we performed a genome-based analysis of ESBL-producing E. coli isolates from surface water samples. Water samples were collected from eleven different surface water sites (lakes, river). ESBL-producing E. coli were recovered from these samples using filters and chromogenic media. Whole-genome sequencing of ESBL-producing E. coli was performed followed by determination of the multilocus sequence type (ST), ESBL-type and virulence genes. Phylogenetic analysis was done using single nucleotide analysis. From all water samples taken, nineteen ESBL-producing E. coli were recovered. All of them harbored an ESBL gene. Nine different multilocus sequence types (STs) were determined, among which ST-949 was the ST detected most frequently. Phylogenetic analysis of ST-949 isolates revealed that all those isolates were closely related. In addition, they harbored an identical chromosomal insertion of blaCTX M 15, indicating a clonal relationship among these isolates. Genetic comparison with isolates from all over the world revealed that these isolates were closely related to human clinical isolates derived from New Zealand and Sweden. An ESBL-producing E. coli ST-949 clone was detected in German surface waters. Its close relationship to human clinical isolates suggests its ability to colonize or even infect humans. Our findings reveal that water sources indeed may play a hitherto underreported role in spread of ESBL-producing isolates.